2011
DOI: 10.1002/j.0022-0337.2011.75.6.tb05099.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Predoctoral Dental Education and Practice Patterns in Special Care Dentistry

Abstract: The objective of this research project was to compare alumni perceptions of predoctoral dental education in the care and management of patients with complex needs to alumni practice patterns. Alumni from the University of the Paciic Arthur A. Dugoni School of Dentistry who graduated from 1997 to 2007 were surveyed regarding perceptions of their predoctoral education in the care of patients categorized and deined as medically compromised, frail elders, and developmentally disabled, as well as their practice pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 10 publications
4
49
1
Order By: Relevance
“…Thus, while the programme seemed to be able to help improve students' reactions to people with special healthcare needs, it proved unable to lower the barrier when it comes to treating them. This contrasts with results of previous studies with dental students as well as with practicing dentists which revealed a positive association between the exposure to education in the treatment of persons with special healthcare needs and the willingness to treat this clientele (see Introduction). A possible explanation for this discrepancy as well as for the increasing endorsement of specialised services may be sought in students' growing awareness that they were insufficiently prepared for treating this clientele.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, while the programme seemed to be able to help improve students' reactions to people with special healthcare needs, it proved unable to lower the barrier when it comes to treating them. This contrasts with results of previous studies with dental students as well as with practicing dentists which revealed a positive association between the exposure to education in the treatment of persons with special healthcare needs and the willingness to treat this clientele (see Introduction). A possible explanation for this discrepancy as well as for the increasing endorsement of specialised services may be sought in students' growing awareness that they were insufficiently prepared for treating this clientele.…”
Section: Discussioncontrasting
confidence: 99%
“…Apart from a lack of clinical proficiency, unfamiliarity with this clientele may foster misconceptions and negative stereotypes, resulting in reluctance to treat patients with special needs for dental care. In fact, several studies have shown that dentists who had undergone training in managing patients with special healthcare needs and who perceived their educational experiences as valuable felt more comfortable with treating this group of patients and treated more of these patients compared to those not exposed to this kind of training . Similarly, students who perceived themselves prepared for the treatment of patients with special needs showed greater future intention to treat this clientele …”
Section: Introductionmentioning
confidence: 99%
“…This could be due to extra time and patience needed to manage this cohort [15]. It has also been documented that dentists who had undergone training in SND during their undergraduate years treated more patients with special needs and had better attitudes towards providing care for this population, compared to dentists who were not exposed to such training experience at the undergraduate level [52][53][54]. It is evident in the present study that high percentage of respondent provided treatment for patients with special needs as they were exposed to SND training at undergraduate level.…”
Section: Discussionmentioning
confidence: 99%
“…Chavez et al . ( 24 ) reported in 2011 that those dentists that have been prepared to treat patients with special needs during their education are more prone to treat them after university. There are some other additional factors that influence whether the dentist would treat or not these patients, such as the low compensation rates combined with the complex management issues and additional time and staffing that are required in special care dentistry.…”
Section: Discussionmentioning
confidence: 99%